2001
DOI: 10.1074/jbc.c100351200
|View full text |Cite
|
Sign up to set email alerts
|

Linking Global Histone Acetylation to the Transcription Enhancement of X-chromosomal Genes in Drosophila Males

Abstract: It has become well established for several genes that targeting of histone acetylation to promoters is required for the activation of transcription. In contrast, global patterns of acetylation have not been ascribed to any particular regulatory function. In Drosophila, a specific modification of H4, acetylation at lysine 16, is enriched at hundreds of sites on the male X chromosome due to the activity of the male-specific lethal (MSL) dosage compensation complex. Utilizing chromatin immunoprecipitation, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
150
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(164 citation statements)
references
References 36 publications
(48 reference statements)
14
150
0
Order By: Relevance
“…Our observation that there is no more polymerase on the X chromosome than autosomal sequences is consistent with previous suggestions that the DCC does not increase the amount of polymerase loading or promoter clearance, but rather the speed at which a transcript is completed (i.e., transcription elongation) (Smith et al 2001). Our detection of negligible amounts of DCC on promoters further supports this conclusion.…”
Section: Mechanism Of Dosage Compensationsupporting
confidence: 81%
See 2 more Smart Citations
“…Our observation that there is no more polymerase on the X chromosome than autosomal sequences is consistent with previous suggestions that the DCC does not increase the amount of polymerase loading or promoter clearance, but rather the speed at which a transcript is completed (i.e., transcription elongation) (Smith et al 2001). Our detection of negligible amounts of DCC on promoters further supports this conclusion.…”
Section: Mechanism Of Dosage Compensationsupporting
confidence: 81%
“…Pausing has been noted for all RNA polymerases, and is exacerbated on chromatin templates (for review, see Sims et al 2004). The acetylation of H4K16 in the middle and 3Ј end of two X-chromosomal genes suggests that H4K16 acetylation may follow a similar pattern to the DCC within genes themselves (Smith et al 2001). We have shown that H4K16 acetylation is very similar to the binding of the DCC at intermediate, restriction fragment resolution.…”
Section: Mechanism Of Dosage Compensationmentioning
confidence: 72%
See 1 more Smart Citation
“…Intriguingly, run is one of the X-linked genes with SXL-binding sites. The run gene does not accumulate H4Ac16 in males, and run expression is not decreased in roX1 À roX2 À or msl males (supplemental Tables S4 and S5 at http://www.genetics.org/supplemental/; Smith et al 2001). While this suggests that run is likely to be compensated in females by SXL, about half of the Xlinked genes that display multiple SXL-binding sites do decrease in roX1 À roX2 À males, indicating at least a partial regulation by the MSL complex (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This complex assembles only in males because msl2 RNA is not translated in females (Kelley et al, 1997). Acetylation of nucleosomal histones on the male X chromosome is thought to facilitate transcriptional elongation approximately twofold (Smith et al, 2001). We investigated genetic interactions between the msl and mle mutations, and vg-Fbz, which shows a male-limited wing phenotype.…”
Section: Mutations In Dosage Compensation Loci Enhance the Vg-fbz Malmentioning
confidence: 99%